Morfološka struktura izvedenih atributivnih imenica i semantički odnosi sa upravnom riječju imeničke sintagme u savremenom engleskom jeziku (Philologia, 2021)
Derived nouns are formed by means of derivational suffixes attached to nouns, adjectives and verbs. It is a well-known fact that derivational suffiixes guide the meaning of the derived noun toward already determined semantic patterns. Guided by the known fact that premodifying nouns bring dense packaging of information into the phrase structure, not always easy to interpret, the main aim was to see how much morphological structure of derived premodifying nouns can infulence the guidance and eventually interpretation of the information. In the end, after descriptive and analytic analysis of examples taken from the newspaper register, we conclude that derived nouns express the most versatile meaning-relationships with the phrase head and that morphological structure does not greatly influence guidance and final interpretation of those meaning-relationships. Some of these meaning-relationships can be predicted due to used derivational suffixes because they always lead to the same phrase meaning-relationships, but in many examples the same suffix did not lead to the creation of the same meaning-relationship which only confirmed how delicate interpreting noun phrase with premodifying nouns can be.
Keywords: noun; noun phrase; morphological classification; semantic relations